The impact of body position on vital capacity among pregnant women in the second trimester - Al Zhranei, Raid; Alsulami, Shatha; Alfaydi, Weam; Alzahrani, Reem; Alsulami, Maher; Al Nufaiei, Ziyad F. (Frontiers in Medicine, 2024)
Background: Pregnancy introduces significant physiological changes, notably impacting respiratory dynamics, especially during the second trimester. Data remain inconclusive about how body posture might influence lung function in pregnant women. We aimed is to examine the impact of body position on slow vital capacity in pregnant women during their second trimester.Methods: This observational study was carried out at King Khalid Hospital in Saudi Arabia, involving pregnant women in their second trimester, from 14 to 26 weeks of gestation. We utilized the KoKo® Legend Portable Office Spirometer to measure slow vital capacity (SVC) in both sitting and standing positions. Participants' demographic details were recorded, ensuring a comprehensive analysis that accounted for age, BMI, and gestational age. Results: Among a total of 136 pregnant women, the majority (61.8%) were aged between 22 and 29 years, with 39% falling into the overweight category based on their BMI. The analysis of SVC revealed no statistically significant difference between sitting (M=2.31L) and standing (M=2.33L) positions, p=0.24, indicating that body posture does not significantly impact SVC in the second trimester of pregnancy. Conclusion: Our findings suggest that while body posture may not be a critical factor in managing respiratory dynamics during pregnancy, personalized care remains essential. Future research should broaden its scope to include a wider range of participants and consider additional factors such as physical activity levels and overall health profiles to develop targeted recommendations for maternal and fetal health.